Development of Computer-Aided Media Operating Materials Calculate Integers - Juliana Margareta Sumilat; Hetty J. Tumurang; Gabrielia Suleman; Noldy Posumah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This study aims to develop computer-assisted learning media for integer arithmetic operations for fourth-grade students in elementary education. The research method used is the Luther-Sutopo version of the development method or better known as Research and Development (R&D). This research is limited to only 5 steps from stage 1 to stage 5, namely Concept, Design, Material Collecting, Assembly, and Testing (Validation, Revision, and Trial). Development of computer-assisted learning media on this integer arithmetic operation material in the form of instructional videos. After going through the process of testing media experts, material experts, and the revision process and field testing in class IVa SD Negeri 2 Tomohon, the average learning outcome was 83.84. Achievement of average learning outcomes is in the category of excellent learning outcomes. Then the results of the attractiveness trial showed the percentage of the mean value of the student's response was 91.35 with very attractive criteria. Thus it is concluded that the computer-assisted learning media on integer arithmetic operations are feasible.